The ClinGen Epilepsy Gene Curation Expert Panel—Bridging the divide between clinical domain knowledge and formal gene curation criteria. Issue 11 (11th October 2018) - Helbig, Ingo; Riggs, Erin Rooney; Barry, Carrie‐Anne; Klein, Karl Martin; Dyment, David; Thaxton, Courtney; Sadikovic, Bekim; Sands, Tristan T.; Wagnon, Jacy L.; Liaquat, Khalida; Cilio, Maria Roberta; Mirzaa, Ghayda; et al.
Abstract: The field of epilepsy genetics is advancing rapidly and epilepsy is emerging as a frequent indication for diagnostic genetic testing. Within the larger ClinGen framework, the ClinGen Epilepsy Gene Curation Expert Panel is tasked with connecting two increasingly separate fields: the domain of traditional clinical epileptology, with its own established language and classification criteria, and the rapidly evolving area of diagnostic genetic testing that adheres to formal criteria for gene and variant curation. We identify critical components unique to the epilepsy gene curation effort, including: (a) precise phenotype definitions within existing disease and phenotype ontologies; (b) consideration of when epilepsy should be curated as a distinct disease entity; (c) strategies for gene selection; and (d) emerging rules for evaluating functional models for seizure disorders. Given that de novo variants play a prominent role in many of the epilepsies, sufficient genetic evidence is often awarded early in the curation process. Therefore, the emphasis of gene curation is frequently shifted toward an iterative precuration process to better capture phenotypic associations. We demonstrate that within the spectrum of neurodevelopmental disorders, gene curation for epilepsy‐associated genes is feasible and suggest epilepsy‐specific conventions, laying the groundwork for a curation process of all major epilepsy‐associated genes. Abstract : Epilepsy is emerging as a frequent indication for diagnostic genetic testing. The ClinGen Epilepsy Gene Curation Expert Panel is tasked with connecting the domain of traditional clinical epileptology and the rapidly evolving area of diagnostic genetic testing. We identify precise phenotype definitions and phenotypic boundaries, gene selection strategies, and rules functional models for seizure disorders as critical components of the gene curation process. We demonstrate that curation for epilepsy‐associated genes is feasible and suggest epilepsy‐specific conventions.